Night at the Museum 2: Battle of the Smithsonian - 1978-; Hader, Bill; Gervais, Ricky; Coogan, Steve; Bernthal, Jon.; 1958-; Chabat, Alain; 1968-; Cherry, Jake; 1996-; Malek, Rami.; Peck, Mizuo; et al. (Beverly Hills, CA, 2009)
Security guard Larry Daley infiltrates the Smithsonian Institute in order to rescue Jedediah and Octavius, who have been shipped to the museum by mistake.
Keywords: Smithsonian Archives; Drama; Museums; Video recordings for the hearing impaired; Drama; Washington (D.C.); Deaccessioning; Drama; Employees; Washington (D.C.); Museums; Washington (D.C.); Museum storage facilities; Drama; Fantasy films; Action and adventure films; Comedy films; Feature films